Numerical Study of Instabiities in Magnetized Inhomogeneous Plasmas under the Effect of Ionization. Issue 2 (February 2016) - Chaudhary, J.
Abstract: Influence of ionization is studied on two stream instability (TSI) in an inhomogeneous plasma in the presence of obliquely applied magnetic field. In addition to the usual TSI, a new type of instability is found to occur in this system, which is driven by the magnetic field and survives for relatively longer wavelength of oscillations. The growth rates of both the instabilities are enhanced by the magnetic field but their magnitudes attain a minimum value at certain angles of the wave propagation depending upon the wavelength of oscillations. At a critical value of ionization rate there is a sudden fall in the growth of both the instabilities, the reason of which is understood as the Landau damping. A further enhancement in the ionization suppresses the usual TSI whereas the magnetic field‐driven instability attains much lower growth. This new type of instability grows faster in the plasma having heavier ions, but shows a weak dependence on the charge of the ions. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)